Static harmony and dynamic tension in abstract sculpture - Fedorenkova S. A. (Science, education, society: trends and prospects, 2024)
The article explores the interaction of static harmony and dynamic tension in abstract sculpture, viewing them as a dialogue of opposites that enriches the perception of art. Static elements, associated with peace and stability, are contrasted with dynamic ones, conveying movement and variability. This interaction creates a complex emotional connection between the viewer and the work, revealing the depth of meaning and versatility of artistic expression. The analysis shows how the use of different forms, materials and compositional techniques allows artists to effectively navigate this dialogue, creating works that reflect the complexity of the modern world. The article is relevant in the context of rethinking traditional frameworks in contemporary art.
Keywords: современное искусство; динамика; художественный образ; скульптура; sculpture; dynamics; abstraction; artistic image; абстракция; Contemporary art; статика; statics